Incorporating Customer Requirements in Assessing Criteria Based On Triz - A Case Study - Faiz, Mohd Turan (Asian Research Publishing Network (ARPN), 2016)
In order to remain competitive in today’s technologically driven world, companies try to determine the optimal settings of design attribute of new products from which the best customer satisfaction can be obtained. Identification of customer requirements is the starting point of design process. Most of design approaches focus on technical domains to define customer requirements. However, the success of product design nowadays goes beyond technical features; it often depends heavily on multi-facets of customers’ needs including various business parameters. In this paper, a method of incorporating customer requirements for criteria assessment in design evaluation process has been developed. The first stage of the methodology selects the criteria and identifying parameters. The second stage calculates the weight of TRIZ (an acronym for the Theory of Inventive Problem Solving). Case examples from industry are presented to demonstrate the efficacy of the proposed methodology. The result of the example shows that the application of TRIZ in assessing criteria by incorporating customer requirements provides an alternative to existing methods.